Dung beetle assemblage changes along a chronosequence in a recovering tropical dry forest - Jibram León; Daniel González-Tokman; Teresa Castillo-Burguete; Víctor Manuel Vidal-Martínez; José Luis Hernández-Stefanoni; Carlos N. Ibarra-Cerdeña (PLoS ONE, 2025)
Tropical dry forests are among the most threatened ecosystems globally, facing extensive degradation from land-use change. Understanding how biodiversity responds during forest regeneration is critical for conservation and sustainable land management. We assessed the community composition and functional diversity of dung beetles (Scarabaeinae) across a forest recovery chronosequence (1–100 years) in the Yucatán Peninsula. The study area is characterized by traditional Mayan agroforestry systems that shape the landscape. 90 pitfall traps were set up across six forest age classes and were collected 6,605 individuals from 23 species and 13 genera. Dung beetle species richness, biomass, and abundance were significantly associated with forest structural, and diversity metrics. Forest Shannon entropy ( H ′), inverse Simpson concentration ( IF ₀, ₂), and aboveground biomass emerged as strong predictors of community attributes. Abundance and biomass responses varied by functional group: small diurnal rollers (SRD) increased with land-use intensity, while large nocturnal rollers (LRN), large diurnal tunnellers (LTD), and small nocturnal tunnellers (STN) declined sharply from mature forests to early successional stages and agricultural areas. Species richness ( 0 D ) peaked in early to intermediate successional stages (5–20 years), whereas dominant species diversity ( 2 D ) was highest in mixed-use forests under moderate disturbance. Distance-based redundancy analysis (db-RDA) and multi-model inference revealed that forest attributes—including DBH, aboveground biomass, canopy openness, and litter depth—jointly explained 48.7% of the variation in dung beetle assemblage structure (p < 0.001). Litter volume was positively correlated with species richness (adj. R 2 = 0.76), and IF₀,₂ was a key predictor of biomass (adj. R 2 = 0.62). Our findings reveal threshold-based and trait-mediated responses of dung beetle assemblages to forest succession, highlighting the ecological importance of bioculturally managed landscapes. These results underscore the role of secondary forests in maintaining biodiversity and ecosystem functions, supporting their conservation as vital components of tropical dry forest recovery.